#STOPASIANHATE: Donald Trump's Political Propaganda Against Asian Racism in the United States - Arofah Minasari; Dini Nurkhasanah; Rahmannisa Kirana; Salma Dewi; Santi Pratiwi (Jurnal Studi Sosial dan Politik, 2021)
During the Covid-19 pandemic, the issue of racism became a hot topic discussed by the world community, especially in the United States. The bustle of the #STOPASIANHATE hashtag illustrates that the issue of racism is attracting the attention of the world community massively. The emergence of this hashtag was triggered by one of the political propagandas of the Former President of the United States, Donald Trump, through his tweet stating that the Covid-19 virus was the "Chinese Virus". Therefore, this paper aims to find out how the influence of Donald Trump's political propaganda on the level of racism among Asian-Americans. In this paper, the authors use qualitative research methods through case studies. The results show that Donald Trump's political propaganda affects the level of racism in the United States with an increase in hate-speech cases against Asian-Americans by 15% during the pandemic compared to 2019.